2004
DOI: 10.1074/jbc.m404982200
|View full text |Cite
|
Sign up to set email alerts
|

Local Control of AMPA Receptor Trafficking at the Postsynaptic Terminal by a Small GTPase of the Rab Family

Abstract: The delivery of neurotransmitter receptors into the synaptic membrane is essential for synaptic function and plasticity. However, the molecular mechanisms of these specialized trafficking events and their integration with the intracellular membrane transport machinery are virtually unknown. Here, we have investigated the role of the Rab family of membrane sorting proteins in the late stages of receptor trafficking into the postsynaptic membrane. We have identified Rab8, a vesicular transport protein associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 73 publications
(70 reference statements)
7
143
0
Order By: Relevance
“…4 A, scheme). As previously published (Gerges et al, 2004), overexpression of EGFP-Rab11-DN the activity-dependent delivery of GluA1-containing AMPARs from intracellular compartments into synapses during LTP (Park et al, 2004;Brown et al, 2007). To evaluate the role of Rab11 in AMPAR synaptic delivery upon cholesterol removal, we used a well-characterized dominant-negative (DN) version has no significant effect on synaptic AMPAR currents under basal conditions (Fig.…”
Section: Synaptic Potentiation Induced By Cholesterol Removal Is Medimentioning
confidence: 99%
“…4 A, scheme). As previously published (Gerges et al, 2004), overexpression of EGFP-Rab11-DN the activity-dependent delivery of GluA1-containing AMPARs from intracellular compartments into synapses during LTP (Park et al, 2004;Brown et al, 2007). To evaluate the role of Rab11 in AMPAR synaptic delivery upon cholesterol removal, we used a well-characterized dominant-negative (DN) version has no significant effect on synaptic AMPAR currents under basal conditions (Fig.…”
Section: Synaptic Potentiation Induced By Cholesterol Removal Is Medimentioning
confidence: 99%
“…Rab8 is known to regulate traffic along the TGN-RE-plasma membrane pathway, but whether this involves traffic into, through or out from the RE is not clear. Rab8 is also involved in AMPA recruitment to dendritic spines from the RE of neurons and thus may serve in both sorting and storage functions of the RE (Huber et al, 1993a;Gerges et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rab8 is known to regulate traffic along the TGN-RE-plasma membrane pathway, but whether this involves traffic into, through or out from the RE is not clear. Rab8 is also involved in AMPA recruitment to dendritic spines from the RE of neurons and thus may serve in both sorting and storage functions of the RE (Huber et al, 1993a;Gerges et al, 2004).Given the diverse roles of Rab8 in a variety of contexts, it could potentially act 1) in the transport of vesicles from the TGN to the RE, perhaps controlling fusion into the RE; 2) in organizing the sorting of basolateral traffic into subdomains of the RE as vesicular traffic enters this structure; or 3) in budding from the RE and delivery of cargo to the plasma membrane, including the penetration of the actin-filament web near the plasma membrane (Peranen et al, 1996;Hattula et al, 2002). In an effort to resolve these issues, we examined the requirement for Rab8 in the polarized sorting of endocytic ligands and secreted proteins in MDCK cells.…”
mentioning
confidence: 99%
“…PSD-95 may also function in the anchoring of GluR1 containing AMPARs, since expression of this protein in hippocampal slice cultures upregulates the amount of GluR1 found in synapses and increases synaptic transmission, occluding LTP (Ehrlich and Malinow, 2004;Gerges et al, 2004). An enhancement of LTP is also observed in PSD-95 knockout mice (Migaud et al, 1998), and similar findings were reported in another deletion mutant of PSD-95 (Beique et al, 2006).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%
“…Also, the mechanisms involved in the regulation of Ras activity that are relevant to its effects in the regulation of AMPAR trafficking remain unknown. Rab8 is a distinct small GTPase that is also necessary for the synaptic delivery of GluR1-containing AMPARs induced by a constitutively active form of CaMKII, overexpression of PSD-95 and induction of LTP in cultured hippocampal slices (Gerges et al, 2004). Rab8 is present in both trans-Golgi network and recycling endosomes (Ang et al, 2003), but it was proposed that the effects of this small GTPase on LTP occur at the level of the former compartment (Gerges et al, 2004).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%